Effects of Health Literacy Promotion Program on the 3O. 2S. Self-Care Behavior and Health Literacy of the Elderly at Risk of Diabetes Disease, Sam Ngam Tha Bot Subdistrict, Hanka District Chainat Province - Watthana, Sasima; Yotthongdi, Naphatsorn; Nunla-ong, Yutdhna; Jaisan, Piyaporn (Journal of Preventive Medicine Association of Thailand, 2024)
Objectives: To study effects of health literacy and health behavior promotion on the 3O. 2S. Self-care behavior and health literacy of the elderly at risk of diabetes disease Before and after participating in the health literacy program. Methods: This was a quasi-experimental research Nutbeam's framework of health literacy to develop a health promotion program. The researchers used the simple random method. and determine the characteristics of a sample group of 30 people. They will receive care as stated by the 6-weeks health literacy promotion program and assess self-care behavior according to 3O. 2S. self-care behavior and health knowledge of risk. The groups before and after participating in the program were analyzed with descriptive statistics and an Independent Sample t-test. Results: The sample group had mean score of the 3O. 2S. self-care behavior and health literacy. The intervention group had a significance higher score than those of the control group (p<.05). Conclusions: Promoting health literacy in response to the causes of health-risk behavior makes people at risk of diabetes more likely to change their behavior for the better. Therefore, the health team could involve a health literacy promotion program from this research to systematize health promotion activities for people at risk of diabetes to have good health.